Biografi Kolektif Pemikir Jawa sebagai Pionir Psikologi Nusantara: Soemantri Hardjo Prakoso, Ki Ageng Suryomentaram, R.M.P. Sosrokartono, dan Mohammad Subuh - Suci, Eunike Sri Tyas (Jurnal Sejarah Citra Lekha, 2025)
Psychology as it has been taught in Indonesia has largely followed Western frameworks, grounded in Western modes of thought considered modern, namely, the scientific study of individual mental processes. Scientific inquiry in this tradition relies on empirical and objective methods, allowing findings to be tested and replicated. Historically, however, the early development of psychology in Indonesia was more pragmatic, emerging primarily from psychometric training courses rather than from a systematic engagement with psychology as a scientific discipline in line with established epistemological standards. This historical trajectory raises a critical and reflective question: Is there a form of psychology, or ilmu jiwa, rooted in Eastern values within the archipelago? And what distinguishes it from Western psychology? These questions form the foundation of the author’s historical and academic exploration, with a particular focus on Javanese thought. Javanese perspectives were chosen as the primary focus due to the relative accessibility and availability of relevant literature. Accordingly, this study first examines what is termed Nusantara Psychology. Through a careful review and verification of sources, the author focuses on four Javanese thinkers: Soemantri Hardjo Prakoso, Ki Ageng Suryomentaram, Panji Sosrokartono, and Muhammad Subuh. These thinkers share a defining characteristic that sets their conceptualizations of the human psyche apart from Western psychology: the central role of spirituality in understanding human psychological life. The psychological frameworks developed by these Javanese thinkers are expected to contribute to the future development of Indigenous Psychology as well as Indonesian Psychology (Psikologi Indonesia). Further research is encouraged to explore non-Javanese thinkers and to conduct comparative analyses, in order to deepen understanding of the mental processes of Indonesian people.